Implementar el sistema de información SIA poas manager 3.0 en la Contraloría Municipal de Armenia. (2015)
The methodology use to do a control on the public entities has been evolving, what this has done is to make better the accountability practices and on the control on the management for each one of the administrations, this is how the application of innovative elements help the efficiency of the actions that need to be done by the part of the high management to complete with the performance that can bring a mechanism that can help with the complement of the goals that were set up. All of this by some standers, policies and procedures interposed by the different organisms perform the controls by the entities of governmental order applying tools like information system SIA POAS Manager, a standard tool design by the general audit of the republic that lets set up action plans for the validity for each one of the administrative management where all the process of the existing contraluria municipal of Armenia participle. Taking place the inclusion of the activities necessaries to have complete, with the respective controls and tracing, generating synergy on what planned for each process by the high management what is going to do is making better the management efficiency and the fulfillment of the institutional rules that include the normalization of all the authorities of the public administration strengthening the management on all the aspects with his strategic deployment.